Fastabiq al-khairat: Wujud Etika Profesi Berkeadilan - Aripratiwi, Ratna Anggraini (IAIN Kudus, 2023)
This study aims to cultivate the spirit of Fastabiq al-khairat, a competition in goodness, as the foundation for professional ethics in public accounting. The Public Accountant Professional Code of Ethics (KEPAP in Indonesia), issued by IAPI, serves as the basis for the implementation of accounting work. The principles outlined in the code of ethics still tend to be world-centric, highlighting the importance of incorporating Divine values into professional practices. To explore this, the study employs Islamic ethnographic methods, conducting interviews with participants and analyzing their values through the lens of Fastabiq al-khairat. The study proposes instilling the spirit of Fastabiq al-khairat into the fundamental principles of professional ethics, with intention as the cornerstone. The implication of this research is to offer an alternative perspective distinct from the Western benchmark used to gauge ethical behavior success. By integrating the values of Fastabiq al-khairat into the core principles of accounting professional ethics, a just and fair ethical framework can be established for fulfilling mandates and responsibilities. The anticipated outcome of this research is to introduce the concept of Islamic values, specifically Fastabiq al-khairat, as a guiding force in the development of professional ethics within the field of public accounting.